Invasive Papillary Bladder Carcinoma in a Golden Retriever Dog and its Surgical Management - Mahesh, V.; N.S. Saritha (The Indian Veterinary Journal, 2026)
A 12-year-old male Golden Retriever dog was presented to the Pet Connect speciality hospital with the complaint of blood in urine, stronguria and pollakiuria. Ultrasonography revealed moderately distended, irregular bladder wall thickening and cauliflower like mass with mixed echogenicity and an enlarged prostate gland. Cystotomy was performed to excise the mass attached to the bladder wall and to remove bladder stones. Bilateral orchiectomy was also performed. The histopathological examination of the mass revealed a high-grade invasive papillary urothelial carcinoma with a micropapillary pattern. This report describes the surgical management of invasive papillary bladder carcinoma in a Golden Retriever dog.